PERKEMBANGAN DAN TANTANGAN INDUSTRI TEKNOLOGI FINANSIAL INDONESIA DI ERA EKONOMI DIGITAL - Andriariza, Yan; Agustina, Lidya (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2020)
The industry of financial technology, also known as the fintech industry, is one of the sectors that are currently developing in Indonesia. Even though this industry is one of the fastest-growing industries, there are some challenges faced by players in the industry. The purpose of this study is to map the problems and challenges. Besides that, this study also aims to define the strategies that can be used to solve the issues. This study is using a qualitative method, with FGD, in-depth interview, and literature study as data collection methods. The results of this study indicate that the challenges faced by the fintech industry derived from the technology itself, the condition of society in Indonesia, and coordination with related stakeholders. Strategies that can be taken to overcome these challenges are the development of policies through the 5Ps scheme based on business development strategies, and also the development of the ecosystem of the financial sector in Indonesia.